2012
DOI: 10.3892/ijo.2012.1750
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-A1 mRNA is associated with poor prognosis of colorectal cancer

Abstract: We previously studied hypoxic tumor cells from hepatic metastases of colorectal cancer (CRC) and determined several potential prognostic factors, including expression of ephrin-A1 (EFNA1), which was highly induced by hypoxia. Here, we further evaluated the prognostic impact of EFNA1 expression. Samples from a total of 366 CRC patients from 11 institutes were analyzed by either microarray (n=220) or quantitative reverse-transcriptase polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…In line with the results of the present study, hypoxic conditions are known to upregulate the expression of EFNA1 in hepatoma cells in vitro (34,35). We previously reported that silencing of EFNA1 in tumor cells inhibits the migration, invasion and proliferation of tumor cells themselves and also inhibits the migration of endothelial cells in coculture experiment (32). Thus, EFNA-mediated interactions between the endothelium and surrounding cells may be critical for vascular sprouting and the penetration of vessels into tumor tissues.…”
Section: Discussionsupporting
confidence: 77%
“…In line with the results of the present study, hypoxic conditions are known to upregulate the expression of EFNA1 in hepatoma cells in vitro (34,35). We previously reported that silencing of EFNA1 in tumor cells inhibits the migration, invasion and proliferation of tumor cells themselves and also inhibits the migration of endothelial cells in coculture experiment (32). Thus, EFNA-mediated interactions between the endothelium and surrounding cells may be critical for vascular sprouting and the penetration of vessels into tumor tissues.…”
Section: Discussionsupporting
confidence: 77%
“…FGF-BP increases tumorigenicity and is highly expressed in colon carcinoma [64] TGM2 (transglutaminase 2) Elevated expression is found in compact spheroid formation by ovarian cancer cells [65] C. Transcripts down-regulated by resveratrol and up-regulated by IL-6 EFNA1 (Ephrin A1) It binds to the Eph A2 tyrosine kinase receptor, which drives migration and invasion of colorectal cancers. Its mRNA expression correlates with poor prognosis in hepatocarcinoma and colorectal cancers [41,66,67] THBS4 (thrombospondin 4) It is a stromal protein involved in cellular migration, adhesion, and attachment that has been shown to play a role in metastatic progression of lung, breast, and colorectal cancers [68][69][70] SGK1 (serum and glucocorticoid regulated Kinase 1)…”
Section: Il-6 and Resveratrol Modulate The Transcriptome And The Micrmentioning
confidence: 99%
“…We used this model to identify the following novel hypoxia-inducible genes: Jumonji domain containing 1A (JMJD1A) (12), adrenomedullin (ADM) (13), ephrin-A1 (EFNA1) (14), procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2) (15) and secretoglobin, family 2A, member 1 (SCGB2A1) (16).…”
Section: Fructose-bisphosphate Aldolase a Is A Key Regulator Of Hypoxmentioning
confidence: 99%